Debates sobre o retorno financeiro do capital humano: o aumento da escolaridade das mulheres foi capaz de reduzir o hiato salarial de gênero? Brasil/2008 - Alan Araújo Freitas (2013)
The average wage gap between men and women is well known. The wage inequality between men and women across the income distribution is, however, unknown in Brazil. The goal of this dissertation is to evaluate the income gender gap of individuals who are in the labor market conditioning the differences on their levels and types of: human capital,occupation, social capital, cultural capital and marital status over the wage distribution of men and women. The following questions guide the study: To what extent the increased education of women was able to reduce the gender wage gap? Could be argued that the income gap is larger at upper levels of the income distribution? To answer these questions we used data from the Instituto do Milênio, 2008. The results show that after controlling for other attributes, women earn on average 54% of men's wages. This gender gap is practically the same of fifty years ago, estimated at 60%. The last percentile of wage income showedgreater gender inequality. At the 99th wage percentile, women earn 44% of what is earned by men.